Which aspects of Child Development are Related to the Home Environment? : A Narrative Review - Somaye Kavousipor (Shiraz University of Medical Sciences, 2019)
Background: The home environment is the first context where children have experience, so in the present review article, important aspects of the child development that are influenced by home environment are analyzed, and common questionnaires were used to evaluate them. Review of Literature: The method applied in the present study was a narrative review. Initially, a variety of different sources were employed to find the related literature. The sources included; web-based browsers of Science Direct, PubMed, Scopus, ProQuest & Google Scholar, OT Seeker, Magiran and Iranmedex with keywords combination of "Development", "child", "home environment", "Measurement "&"Questionnaire" and word related to Medical Subject Headings (MeSH) adaptation. A total of 13 articles were included to be studied in detail in order to find the impact of home environment on the child developmental skills, including cognition, movement, emotion and interaction with regard to common home environment measurement. Discussion: All aspects of the home environment such as; physical space, toys, play, and learning materials, and child-adult interaction relationship stimulate motor, emotional and cognitive development and are influential on child developmental skills. The home environment is dependent on family culture, ethnicity, social economic status, and poverty. Conclusion: Most common questionnaires (The Home Observation for Measurement of the Environment (HOME) in domains of cognitive and social development and the Affordance in the Home Environment for Motor Development (AHEMD) in the domain of motor development) were set up to evaluate the home environment.